2020
DOI: 10.1088/2053-1591/ab761b
|View full text |Cite
|
Sign up to set email alerts
|

Exploring dynamics of resonance energy transfer in hybrid Quantum Dot Sensitized Solar Cells (QDSSC)

Abstract: Graphene based nanomaterials are known to provide new avenues to improve semiconductor based light harvesting devices. This work makes use of graphene quantum dots (GQD) to improve the efficiency of a CdSe Quantum Dot Sensitized Solar Cell (QDSSC) by Förster Resonance Energy Transfer (FRET) mechanism. FRET describes non-radiative energy transfer between two adjacent molecules typically in range from 1 to 10 nm with one molecule as donor and other molecule as acceptor. If the acceptor is in close proximity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Copyright 2020 Author(s). 88 (i) UV-VIS spectroscopy. Reprinted with permission from Naik et al, J. Nanostruct.…”
Section: Synthesis Strategies For Gqdsmentioning
confidence: 99%
“…Copyright 2020 Author(s). 88 (i) UV-VIS spectroscopy. Reprinted with permission from Naik et al, J. Nanostruct.…”
Section: Synthesis Strategies For Gqdsmentioning
confidence: 99%
“…After three rounds of dip coating, the thickness of TiO2 the film was 7–8 μm; it increased by approximately 2.5 μm after each cycle. A hybrid SC with graphene quantum dots (GQDs) has been modeled as an energy donor for CdSe‐sensitized TiO2 SCs; [128] spectral matching, photoluminescence, and lifetime measurements demonstrated that the resulting improvement in the efficiency of the CdSe‐based SCs was due to a non‐radiative energy transfer mechanism. The unit manufacturing was achieved with various CdSe dip‐coating configurations.…”
Section: Fabrication Of Cdse Qdsscsmentioning
confidence: 99%
“…In this case, GQDs mainly acted as a charge recombination suppressor, as electron impedance spectroscopy and transient photovoltage decay measurements confirmed; after optimizing the GQD coating deposition in terms of deposition sequence, concentration, and time, the final devices offered an improved PCE of 6.59% under AM 1.5G full one sun illumination. Recently, PL quenching and lifetime measurements revealed that, in the case of GQDs/CdSe quantum dots, it is also possible to identify the FRET mechanism, so as to gain deeper knowledge of the system, aiming at further performance improvements [ 185 ]. Similar results were recently reported by Kolay and collaborators for a different design centered around CdS quantum dots as the main photosensitizer [ 186 ]; the performance was similar in terms of PCE, although the design was more complex in terms of the fabrication protocol.…”
Section: Gqd Applications In Energy-related Applicationsmentioning
confidence: 99%